MINAT SISWA PUTERI TERHADAP MATA PELAJARAN PENJASORKES DI SD NEGERI 23 MESKOM KECAMATAN BENGKALIS - Iskandar, Iskandar; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT. SD Negeri 23 Meskom District of Bengkalis is one of the schools that implement Penjasorkes learning process, but in the implementation of learning penjasorkes, there are students who are less enthusiastic in following these subjects, particularly the female student. This situation is possible because of many factors, including the lack of student motivation, background penjasorkes teacher education, the teacher Penjasorkes modification, facilities and infrastructure in Penjasorkes learning, support principals, and curriculum and teaching Planning. This research is a descriptive that aims to reveal about the picture female student motivation for learning in elementary school penjasorkes 23 Meskom District of Bengkalis. The study population was 47 people. Sampling was done by total sampling technique, so the sample amounted to 47 people. Instruments used to collect data was questionnaire or questionnaires using Guttman scale. Data were analyzed using frequency distribution formula in the form of a percentage. From the data analysis obtained the following results: The level of student achievement interests amounted to 80.74%, it means that the level of achievement of student motivation female against modification of existing PE teaching in primary schools 23 Meskom District of Bengkalis, located on either classification. The level of achievement modification of existing PE lessons in primary schools 23 Meskom District of Bengkalis amounted to 78.63%, it means that the level of achievement of the role of physical education teachers in public primary schools 23 Meskom District of Bengkalis currently on classification sufficient. The level of achievement infrastructure PE Lessons in SD Negeri 23 Meskom District of Bengkalis amounted to 65.61%.Keywords: Interest in Learning Students to PE